When social assistance reproduces social inequality: intimate partner violence survivors' adverse experiences with subsidized housing. Issue 7 (3rd October 2017) - Jeffrey, Nicole K.; Barata, Paula C.
Abstract: This study examined women's experiences using priority-subsidized housing programs for intimate partner violence (IPV) survivors. Interviews with 10 women highlighted that subsidized housing programs, although very important, can impede women's efforts to safely escape abuse. Our analysis explored three negative accounts: subsidized housing programs as stigmatizing, difficult to access and qualify for, and controlling. Results have important implications for improving practices and policies of subsidized housing programs and suggest that: (a) subsidized and nonsubsidized housing should be integrated; (b) eligibility should not be based on extent and timeframe of abuse; and (c) women should be permitted to choose their own housing.